PENGUJIAN TIGA METODE PENGUKURAN BOBOT ISI PADA TANAH GAMBUT - Sinaga, Christina; Nusantara, Rossie Wiedya; Gusmayanti, Evi; Anshari, Gusti Zakaria (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
This research aims to compare the methods of bulk density measurements in peat soils. The methods are ring sample, peat auger, and syringe. The research was conducted in peat soils in Pontianak City. The research was carried out from June to December 2023. Peat samples were the surface peat (0-10 cm). The samples were collected from five plots, and five replications. On average, the value of bulk density measured by the ring sample was 0.27 g cm-3, which is significantly different from bulk density values measured by the peat auger and syringe: 0.11 g cm-3 and 0.09 g cm-3, respectively. Bulk densities of peat auger and syringe are statistically indifferent. Soil compaction during sampling causes the ring sample's high bulk density value. Accordingly, carbon stock calculation based on ring sample bulk density is significantly higher than carbon stocks calculated by bulk densities of auger and syringe. The bulk density measurement with a peat auger took longer because a water displacement approach must measure the sample volume. Collecting bulk-density samples with a syringe is the easiest and fastest. The volume of the syringe sample is only 10 cm3, and the sample can be taken until the mineral substratum. The number of sample collected by syringe can be significantly increased at 5 cm sampling interval, or equals to 10 sub-samples per 50 cm peat core. Pearson linear correlations of these three methods are sufficiently strong.